Você nunca será uma mulher de verdade” – efeitos de sentidos nas tiras de Muriel Total - Vaillões, Silvana de Araújo (2022)
This text aimed to understand the effects of meaning addressed in the comic strips of the series Muriel Total, by the trans author Laerte. For this, we based ourselves on the theory of Discourse Analysis, French-oriented, effected by Pêcheux (1995; 2006; 2011), Orlandi (2009; 2011; 2017) and Mariani (1996), among others, which considers that the subjects are constituted in their discourse, crossed by ideology, which questions them as subjects. Besides, to effect the analyses, we considered authors who address gender as a process of discursive constitution, namely: Bento (2006; 2008), Butler (2011; 2018), Foucault (1984; 1985; 1988), Lanz (2015), among others. The series Muriel Total was broadcast, for a short period, in the newspaper Folha de São Paulo, having, afterwards, been allocated in a virtual space of the author. It comprises more than eight hundred strips, which, in general, deal with various themes involving transgenderism, in this case, carried out by Muriel, who was Hugo Baracchini. In order to develop the study, we surveyed the theory about concepts that were mobilized by the corpus, such as Discursive Formation, Interdiscourse, subject, meaning, ideology, Discursive Memory, Denomination, among others. We also based ourselves on authors who discuss the themes conveyed by the strips of the series, namely, transgeneracy, gender identity, sexual orientation, heterosexuality, heteronormativity, among others. The study path allowed us to perceive the discursive operation regarding trans subjects in the Muriel Total strips so that such discourses would be affiliated to a DF, which we call Gender Binarist, a term presented by Leticia Lanz (2015) in her book O Corpo da Roupa. The specific objectives were about the presentation of the concepts mobilized by the corpus, based on the French DA theory, as well as an explanation about gender issues that may have been considered in the strips of the series. Furthermore, we found the regularities in the corpus, namely the Discursive Memories mobilized concerning the transgender subject (the one who conforms to the Gender Binary system; the one who resists the Gender Binary system) as we performed the reading gestures. Moreover, we observe the regularity that produces the effects of meanings about the need for Denomination by this trans subject, whether for sexual orientation, relationship with others, ways of behaving, what to like, among others, which are effected by the affiliation to a Gender Binary DF.